Antecedents of Job Stress and Its Impact on Job Satisfaction - Rizwan, Muhammad; Tariq, Muhammad Adeel; Hussain, Shahzad; Rashid, Rana Muhammad; Hussain, Muhammad Safdar; Khawar, Intizar Hussain (Asian Journal of Empirical Research, 2013)
Achieving the pleasures of successful work place is an art of coping with stress. Job stress is a very substantial issue at work place in this new era of competence. So this research is significantly emphasized on causes and effects of job stress and analyze its impact upon job satisfaction. This study also identifies the root causes of job stress (like work overload, role ambiguity, role conflict) and their influence on employees wellbeing, behavior and contribution towards effectiveness. A questionnaire (scales consisting thirty two items) is developed to assess the relationship between job stress and job satisfaction on the basis of Regression and ANOVA analysis. The findings describe very significant results between the variables. There is a very significant positive correlation between work overload and job stress and same is true for role conflict and role ambiguity. The negative correlation is found between job stress and job satisfaction. All the instruments and scales are taken from the standard sources. The results of study can be beneficial for the wide range of organizations, institutions, companies and departments for the better understanding of behavior and wellbeing of the employee’s. Practical implications of results are also having a very significant importance for training concern organizations. This research suggests the direction for future recommendation on the relationship between job stress and organizational performance more concisely and briefly.